Effects of time-restricted eating without caloric restriction on blood pressure and cardiometabolic profile in non-diabetic adults: a systematic review and meta-analysis of randomized controlled trials - Yi, Xin; Yan, Jie; Daut, Ummi Nadira; Abas, Razif; Raja Muhammad Rooshdi, Raja Abdul Wafy; Yang, Chongshuang; Liu, Canzhang (Frontiers in Nutrition, 2025)
ObjectiveTo systematically evaluate the effect of time-restricted eating (TRE) without caloric restriction (CR) on blood pressure (BP) and cardiometabolic profile in non-diabetic adults.MethodsA comprehensive search of electronic databases identified 978 potentially relevant studies, of which 11 randomized controlled trials involving 653 participants were included in this meta-analysis. All included studies compared time-restricted eating (TRE; 6–10-h daily eating windows) without CR to unrestricted feeding controls. Outcomes assessed included systolic BP (SBP), diastolic BP (DBP), heart rate (HR), fasting blood glucose (FBG), fasting insulin (FINS), homeostasis model assessment of insulin resistance (HOMA-IR), and body mass index (BMI). Weighted mean differences (WMD) and 95% confidence intervals (CI) were calculated using random-effects models.ResultsTRE without CR significantly reduced SBP (WMD = −1.79 mmHg, 95% CI: −3.30 to −0.27, p = 0.02), DBP (WMD = −1.75 mmHg, 95% CI: −3.07 to −0.43, p = 0.01), and HR (WMD = −2.19 bpm, 95% CI: −4.01 to −0.36, p = 0.02). Subgroup analyses showed greater BP reductions in participants with elevated baseline SBP or DBP. TRE also led to significant improvements in metabolic parameters, including reductions in FBG (WMD = −2.65 mg/dL, 95% CI: −3.92 to −1.39, p < 0.0001), FINS (WMD = −2.00 μIU/mL, 95% CI: −3.02 to −0.97, p = 0.0001), HOMA-IR (WMD = −0.58, 95% CI: −0.81 to −0.35, p < 0.00001), and BMI (WMD = −1.59 kg/m2, 95% CI: −2.98 to −0.20, p = 0.03). Heterogeneity across outcomes was negligible to moderate.ConclusionTRE without CR can significantly reduce BP and improve glucose metabolism in non-diabetic adults, particularly in those with pre-existing high BP or high FBG or High FINS. However, TRE does not appear to exert meaningful effects on lipid profiles in the absence of CR, indicating that its cardiometabolic benefits may be selective rather than comprehensive. These findings support the potential of TRE as a non-pharmacological intervention for cardiometabolic health, particularly in populations with elevated baseline risk markers.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD420251052403.